Upaya Pengembangan Pola Agroforestri Tradisional Dusung Sebagai Sumber Pangan Masyarakat - Silaya, Thomas; Pietersz, Juglans H (Universitas Pattimura, 2019)
This study aims to determine the structure and composition of vegetation types in the development of dusung, factors that affect economic aspects, environment, and management in the development of dusung and the optimal benefits of economic, ecological and management aspects to support food security. The research method used in this research is descriptive method with quantitative (positivism) and qualitative (phenomenological) approaches. Determination of the location of the study was done by purposive sampling, and data collection was carried out using open and in-depth interviews. The results showed that the structure and composition of dusung vegetation in Hative village consisted of the tree, pole, weaning and seedling levels, with stratification consisting of stratum A to stratum E. Factors influencing economic, environmental and management aspects in Dusung management were social factors- culture in the form of community wisdom such as sasi and Kewang, Dusung Inheritance / Ownership system, cropping patterns and types of soil in Dusung as well as changes in community lifestyle. The development of the dusung has strengths in the form of various kinds of vegetation such as Eugenia aromatica, Durio zibethinus, Lansium domesticum, Bouea macrophylla, Gmelina molucanna, and Myristica fragrans, possessing fertile soil and accessibility of locations easily accessible; and dusung development opportunities namely marketing aspects that have a positive impact on increasing income for the community.